Comparative Efficacy of BTK Inhibitors in Treatment‐Naïve and Relapsed/Refractory Mantle Cell Lymphoma: A Systematic Review and Meta‐Analysis - Fangfei Xu; Xiuping Zou; Yulin Yang; Kuangguo Zhou; Wei Huang (Journal of Cellular and Molecular Medicine, 2026)
ABSTRACT Bruton tyrosine kinase inhibitors (BTKis) have been employed in the treatment of mantle cell lymphoma (MCL). However, direct comparisons of ibrutinib, zanubrutinib, and acalabrutinib across treatment‐naïve (TN) and relapsed/refractory (R/R) MCL remain limited. This meta‐analysis was intended to evaluate their efficacy, addressing critical gaps in clinical decision‐making. We systematically searched PubMed, Embase, and Cochrane up to January 2025 for studies (RCT/single‐arm) assessing the efficacy of BTKis in MCL patients. Among 70 studies, the pooled CR rate in the TN group was higher than that in the R/R group (76.5% vs. 43.2%). Among TN patients, the CR rate of the regimen incorporating zanubrutinib (95.2% [95% CI 0.893, 1.000]) was significantly higher than that of the regimens containing acalabrutinib or ibrutinib ( p = 0.0042). In the R/R group, the BTKi + anti‐CD20 monoclonal antibody + small‐molecular therapy group presented a better CR rate (68.3% [95% CI 0.546, 0.820]; p < 0.0001). When comparing the monotherapy efficacy of three BTKis in R/R MCL, the results indicated that acalabrutinib exhibited a higher CR rate (43.2% [95% CI 0.339, 0.525]) than zanubrutinib or ibrutinib. In addition, zanubrutinib‐based therapy exhibited a lower pooled rate of haematological toxicities compared to the other two BTKi therapies. This work resolved critical uncertainties in BTKi selection for MCL, demonstrating acalabrutinib's and zanubrutinib's first‐line potential, leading to a meaningful improvement in response rate and a manageable safety profile. Chemotherapy‐free regimen can partially overcome the traditionally unfavourable prognosis associated with R/R MCL. These results provide a roadmap for optimizing MCL therapy. Chemotherapy‐free regimens for MCL based on BTKis warrant further validation in RCTs. These findings may advocate for updated guidelines prioritizing zanubrutinib and acalabrutinib in clinical practice.